Improving adherence to immunosuppression after liver or kidney transplantation in individuals with impairments in personality functioning – A randomized controlled single center feasibility study - Wagner-Skacel, Jolana; Fink, Nadja; Kahn, Judith; Dalkner, Nina; Jauk, Emanuel; Bengesser, Susanne; Mairinger, Marco; Schüssler, Gerhard; Pieh, Christoph; Stadlbauer, Vanessa; Kirsch, Alexander H.; Zitta, Sabine; et al. (Frontiers in Psychology, 2023)
Introduction Although adherence to immunosuppressive medication is the key factor for long-term graft survival today, 20–70% of transplant recipients are non-adherent to their immunosuppressive medication. Objective A prospective, randomized, controlled single-center feasibility study was designed to evaluate the impact of a step guided multicomponent interprofessional intervention program for patients after kidney or liver transplantation on adherence to their immunosuppressive medication in daily clinical practice. Materials and methods The intervention consisted of group therapy and daily training as well as individual sessions in a step guided approach. The primary endpoint of the study was adherence to immunosuppression as assessed with the “Basel Assessment of Adherence to Immunosuppressive Medications Scale” (BAASIS). The coefficient of variation (CV%) of Tacrolimus (TAC) through levels and the level of personality functioning was a secondary endpoint. We conducted six monthly follow-up visits. Results Forty-one age- and sex-matched patients [19 females, 58.5 (SD = 10.56) years old, 22 kidney- and 19 liver transplantation] were randomized to the intervention- (N = 21) or control-group (N = 20). No differences between intervention- and control groups were found in the primary endpoint adherence and CV% of TAC. However, in further exploratory analyses, we observed that individuals with higher impairments in personality functioning showed higher CV% of TAC in the controls. The intervention might compensate personality-related susceptibility to poor adherence as evident in CV% of TAC. Discussion The results of the feasibility study showed that this intervention program was highly accepted in the clinical setting. The Intervention group could compensate higher CV% of TAC after liver or kidney transplantation in individuals with lower levels of personality functioning and non-adherence. Clinical trial registration ClinicalTrials.gov, identifier NCT04207125.